2012
DOI: 10.1016/j.puhe.2012.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Depression among caregivers of children with asthma and its impact on communication with health care providers

Abstract: Background Caregiver depression is common, can negatively influence one's ability to communicate with healthcare providers, and may hinder appropriate care for children with asthma. Objective To evaluate the impact of caregiver depression on communication and self-efficacy in interactions about asthma with their child's physician. Study Design Cross sectional analysis using data from the Prompting Asthma Intervention in Rochester–Uniting Parents and Providers study. Methods We enrolled caregivers of chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…(6, 1921) Some studies have been unable to establish a direct link between elevated caregiver burden and increased asthma symptom severity, though this may be due to the complex nature of pediatric asthma management. (18, 22) We found that caregivers of children with a DD reported worse psychological distress, however, there was no significant difference in asthma symptom severity, based on NHLBI criteria, between children with and without a DD. It is possible that our ability to detect differences in asthma severity was limited given that our sample only included children experiencing persistent symptoms.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…(6, 1921) Some studies have been unable to establish a direct link between elevated caregiver burden and increased asthma symptom severity, though this may be due to the complex nature of pediatric asthma management. (18, 22) We found that caregivers of children with a DD reported worse psychological distress, however, there was no significant difference in asthma symptom severity, based on NHLBI criteria, between children with and without a DD. It is possible that our ability to detect differences in asthma severity was limited given that our sample only included children experiencing persistent symptoms.…”
Section: Discussionmentioning
confidence: 63%
“…(18) Although these are logical mechanisms for increased morbidity, (57, 58) recent studies have found mixed results. Several authors have reported that children with depressed caregivers are at increased risk of asthma-related hospitalization, more days with asthma symptoms, and poorer functional status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of our parents reported feeling depressed about their child’s diagnosis, which has been shown to have impact on communication and also satisfaction with the service. In 2012, Fagnano et al [ 30 ] studied parents of children with asthma and the impact of depression on the communication between parents and health care professionals. In that study, 30% of parents had depressive symptoms, and that group was less satisfied with professional visits and felt that their needs were not met.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological distress have also been investigated among caregivers particularly of people with chronic obstructive pulmonary disease [90], patients with psychosis [91][92], patients with schizophrenia [93], cancer patients [94], symptomatic lung cancer patients [95], women with ovarian cancer [96], patients with lung cancer [97][98], and individuals with affective disorders [99]. Studies on psychological distress have also been done on caregivers of children with autism spectrum disorder [100][101][102][103] and children with asthma [104], children with a disorder of sex development [105][106]. However, not much has been done on caregivers of normal preschool pupils in Nigeria generally and in Ekiti State to be specific.…”
Section: Statement Of the Problemmentioning
confidence: 99%